Developing Video Tutorial as Learning Media in Teaching Descriptive Text For Grade X - Lisda Mayasari Saragih; Rahmad Husein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
This research was aimed to Develop Video Tutorial as media of teaching descriptive text for tenth grade SMA Negeri 1 Selesai. This research was applied Research and Development model purpose Gall & Borg (2003) through six steps, there are : gathering data and information, conducting need analysis, designing, experts validating, revising, producing final product. a good learning media is necessity for teachers to have an impact on students and increase their interest in learning, such as a video tutorial as learning media in teaching descriptive text. This media was also practically for students to improving their writing skill because they can open the media at home. Just opened the video from link that has given by the teacher and they can also download it and they can open it for many times. It means this media was flexible. This media can help students to learn descriptive text based on their interest.Keywords: Research and Development (R&D), Descriptive text, Video tutorial